Measurement of vertical fiscal imbalance in Germany - Kowalik, Paweł (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2016)
Regional inequalities are currently a challenge for the majority of countries, in particular large ones, some of which are federations. The federal state system is more complex than the unitary system. This results in specific problems. One of them is the issue of the differing level of economic development of individual territorial units, where the problem of income redistribution emerges. The difference between income and expenses results in the formation of fiscal gaps, both horizontal and vertical. The aim of the paper is to make an attempt to review the literature and to present the measures applied for measuring the vertical fiscal imbalance. It is also the starting point for conducting measurements of those imbalances in Germany based on Bird’s and Tarasov’s methodology. The paper presents the measures applied in the literature for the purposes of measuring vertical fiscal imbalance. In addition, the measurement of those imbalances in Germany are presented
Argumenta Oeconomica, 2016, Nr 2 (37), s. 131-146
Keywords: fiscal imbalance; fiscal gap; measures of vertical inequalities; vertical fiscal imbalance; regional inequalities; federal-regional transfers